2007
DOI: 10.1016/j.regsciurbeco.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and city growth: The role of institutions

Abstract: Abstract. This paper examines how urbanization is accommodated by increases in numbers and in sizes of cities. Political institutions play a key role. Estimation uses a worldwide data set on all metro areas over 100,000 from 1960-2000. The degree of democratization and technological advances strongly affect growth in both city numbers and individual city sizes. Effects on city sizes are heterogeneous. Technology improvements help bigger cities relative to smaller ones. Increasing democratization levels the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(129 citation statements)
references
References 33 publications
13
113
1
2
Order By: Relevance
“…Our results as regards mean reversion are in line with those of Henderson and Wang (2007) and Black and Henderson (2003). However, our findings do not contradict those of other studies employing US data and which conclude that Gibrat's law holds.…”
Section: Nonparametric Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Our results as regards mean reversion are in line with those of Henderson and Wang (2007) and Black and Henderson (2003). However, our findings do not contradict those of other studies employing US data and which conclude that Gibrat's law holds.…”
Section: Nonparametric Analysissupporting
confidence: 88%
“…A non-significant coefficient can be interpreted as being indicative of independence between growth and initial size, supporting Gibrat's law and, therefore, rejecting the mean reversion hypothesis. Black and Henderson (2003) and Henderson and Wang (2007) found that the smallest cities grow fastest, supporting the mean reversion hypothesis; as such, there is some kind of size effect on growth. However, as the main focus of our analysis are new-born cities and the dynamics before the steady state, it might be the case that this size effect can make the time effects less effective.…”
Section: Empirical Analysismentioning
confidence: 60%
“…Audretsch and Feldman [64] emphasize the importance of human capital in the knowledge spillover theory. Henderson and Wang [65] find that democratization and technological sophistication are associated with city growth. In particular, technological advancement has helped large cities more than small ones.…”
Section: Urbanization As a Channel Of Internet Spillovermentioning
confidence: 99%
“…In this subsection I follow Henderson and Wang (2007)-HW henceforth-to select a sample of cities that is comparable across time and countries. They consider metropolitan 6 The model does not distinguish between total and urban population because the rural sector is not explicitly modeled.…”
Section: Selection Of Relevant Citiesmentioning
confidence: 99%